Association of falls and fear of falling with objectively-measured driving habits among older drivers: LongROAD study. (December 2022) - DiGuiseppi, Carolyn G.; Hyde, Hailey A.; Betz, Marian E.; Scott, Kenneth A.; Eby, David W.; Hill, Linda L.; Jones, Vanya C.; Mielenz, Thelma J.; Molnar, Lisa J.; Strogatz, David; Li, Guohua; ,
Highlights: Older drivers with recent falls had more hard braking events in one-year follow-up. Those with high fear of falling drove less and drove nearer home during follow-up. Health, function, medications and demographics largely explained the associations. Falls and fear of falling may serve as markers for crash risk and reduced mobility. Abstract: Objective: Falls in older adults are associated with increased motor vehicle crash risk, possibly mediated by driving behavior. We examined the relationship of falls and fear of falling (FOF) with subsequent objectively measured driving habits. Methods: This multi-site, prospective cohort study enrolled 2990 active drivers aged 65–79 (53% female). At enrollment, we assessed falls in the past year and FOF (Short Falls Efficacy Scale-International). Driving outcomes included exposure, avoidance of difficult conditions, and unsafe driving during one-year follow-up, using in-vehicle Global Positioning System devices. Results: Past-year falls were associated with more hard braking events (HBE). High FOF was associated with driving fewer days, miles, and trips, driving nearer home and more HBE. Differences were attenuated and not significant after accounting for health, function, medications and sociodemographics. Discussion: Differences in objectively measured driving habits according to past-year fall history and FOF were largely accounted for by differences in health and medications. Rather than directly affecting driving, falls and FOF may serve as markers for crash risk and reduced community mobility due to age-related changes and poor health.